Alumina Reinforcement of Inconel 625 Coatings by Cold Gas Spraying - Sergi Dosta; Nuria Cinca; Alessio Silvello; Irene G. Cano (Metals, 2020)
Reinforced Inconel625 coatings have been successfully deposited by means of cold gas spray (CGS). Alumina has been simultaneously sprayed achieving a homogeneous distribution along the deposit with good cohesion between particles. The aim of this study was to investigate whether ceramic reinforcement could improve the mechanical and tribological properties of Inconel625 cold-sprayed coatings, while keeping the oxidation and corrosion resistance capacity. Furthermore, alumina particles were found to improve the spraying feasibility, by avoiding WC nozzle clogging during the process. A proper optimization of the spraying conditions was carried out in order to obtain the lowest possible porosity and best embedment of the alumina. Then, the mechanical and tribological properties as well as corrosion and oxidation behavior were characterized. Alumina acts as a reinforcement, improving the effects of abrasive and sliding wear. Regarding the oxidation and corrosion behavior, the coatings exhibit reasonably good oxidation resistance at temperatures up to 900 °C. The electrochemical corrosion performance in NaCl solution showed potentially lower noble corrosion values and corrosion current densities than bulk Inconel.